Improving Cow Fertility Through Fish Meal Supplementation - Charles R. Staples; Ricardo Mattos; Carlos S. Risco; William W. Thatcher (EDIS)
A goal on most dairy farms is to keep the interval between the time a cow calves and the time she becomes pregnant again as short as possible. Keeping this time interval short, however, is opposed by the high nutritional demands of lactation. The energy required for milk production usually exceeds the energy eaten by the cow in the first couple of months after freshening. Therefore, the cow must rely on the energy stored in her body as fat to help support her milk production. This condition, called negative energy status, can force cows to delay their return to estrus until their diet supplies more and more of their energy requirement. If the negative energy state is severe or prolonged, the number of days open can be excessive and costly. This document is DS-95, one of a series of the Animal Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 7, 2002. Revised July 19, 2005.